Effect of increasing surface roughness on sputtering and reflection - Bizyukov, I.; Mutzke, A.; Schneider, R. (Вопросы атомной науки и техники, 2012)
In this work, the SDTrimSP-2D code was used for numerical simulation of the interaction of ions with a 2D periodical structure as idealized test system to investigate the influence of surface roughness on sputtering. Sputtering yield and reflection coefficient have been studied as a function of the size of the pitch grating structure. Simulations show that the most important changes in ion-surface interactions occur when the structure size gets approximately equal to the size of the collisional cascade.. Код SDTrimSP-2D использовался для моделирования взаимодействия ионов с двухмерной поверхностью, которая взята в качестве идеализированной тестовой системы для исследования влияния шероховатости. Коэффициенты распыления и отражения изучались как функции характерного размера структуры дифракционной решетки. Моделирование показало, что наиболее важные изменения во взаимодействии ионов с поверхностью происходят тогда, когда размер структуры приблизительно равен размеру столкновительного каскада. Код SDTrimSP-2D використовувався для моделювання взаємодії іонів з двомірною поверхнею, яка обрана у якості ідеалізованої тестової системи для дослідження впливу шорсткості. Коефіцієнти розпилення і відбиття вивчалися як функціі характерного розміру структури дифракційної решітки. Моделювання показало, що найбільш важливі зміни у взаємодії іонів з поверхнею відбуваються тоді, коли розмір структури приблизно дорівнює розміру каскаду зіткнень.